Bringing various dimensions of credit of ASEAN countries for scrutiny; implications on sustainable economic growth - Harjito, D. Agus; Mohamed, Zulkifli; Mohamed, Norhayati; Mohd Saat, Nur Ashikin; Zainudin, Zalina (The General Jonas Zemaitis Military Academy of Lithuania, 2020)
This study has used data from the ASEAN region in order to study the relationship among the various dimensions of credit and sustainable economic growth. The objective of this study was to analyze the effects of the credit dimensions on the economic growth for the period 1995-2018. The estimation of regressors was performed on the basis of the one step system of generalized method of moments and the panel corrected standard approach methods. The dynamic and static estimations reveal that the effect of household credit on the economic growth is insignificant whereas business credit, mortgage credit, consumer credit and private sector credit were found to be positive and significant. The current study is original in the sense that the study has been performed with a new dataset and the focus variables are also different. Such studies are important for the ASAEN region as the region is developing as the region is under development, and the level of credit available is one of the primary indicators of the economic performance or ability of a country. Also, this study has used an estimation method that account for the problems of panel data, specifically the issues created by the cross-sections and heterogeneity. The study also has important theoretical and policy-making implications.